Brief Report: Prevalence of Latent Rheumatic Heart Disease Among HIV-Infected Children in Kampala, Uganda. (1st February 2016) - Gleason, Brigette; Mirembe, Grace; Namuyonga, Judith; Okello, Emmy; Lwabi, Peter; Lubega, Irene; Lubega, Sulaiman; Musiime, Victor; Kityo, Cissy; Salata, Robert A.; Longenecker, Chris T.
Abstract : Abstract: Rheumatic heart disease (RHD) remains highly prevalent in resource-constrained settings around the world, including countries with high rates of HIV/AIDS. Although both are immune-mediated diseases, it is unknown whether HIV modifies the risk or progression of RHD. We performed screening echocardiography to determine the prevalence of latent RHD in 488 HIV-infected children aged 5–18 in Kampala, Uganda. The overall prevalence of borderline/definite RHD was 0.82% (95% confidence interval: 0.26% to 2.23%), which is lower than the published prevalence rates of 1.5%–4% among Ugandan children. There may be protective factors that decrease the risk of RHD in HIV-infected children. Abstract : Supplemental Digital Content is Available in the Text.